A New Eco-Friendly Approach for Smart Composite Structures Based on Carbon Nanotube Fibres - Attaf, Brahim (New Environmentally-Friendly Materials, 2025)
In the global nanocomposites market, carbon nanotubes (CNTs) are gaining significant attention due to their potential for revolutionary, high-performance applications. However, proactive measures are still required to ensure their safe use across the entire life cycle, minimizing environmental and health risks. To address these challenges and meet sustainability goals and ecodesign standards, this paper proposes a balanced, eco-friendly approach based on a key performance indicator (KPI), referred to as the ecological factor (eco-factor). This eco-factor will integrate environmental, health, and quality considerations across all stages of the life-cycle assessment, including material selection, characterization testing, theoretical modelling, finite-element analysis, manufacturing processes, maintenance and repair strategies, material recovery and recycling, and energy consumption. By promoting a transparent regulatory framework, well-defined safety requirements, and a stable legal environment, this approach aims to enhance the global competitiveness of future CNT-reinforced nanocomposites in the fields of nanotechnology and advanced materials. With this idea as an objective, our techno-scientific approach could become a normative tool for qualification and certification of future eco-products based on CNT materials, thus guaranteeing their sustainability in terms of economic, environmental and societal conditions. Furthermore, eco-technological action constitutes our primary objective for the coming years and will be pursued through the development of new regulatory requirements, codes, and ecological standards that promote safe and sustainable production within a circular economy framework. This approach is expected to enhance the competitiveness of CNT-based composite companies committed to implementing effective environmental management systems.